Development Study of Turbulent Îº-Îµ Model for Recirculation Flow III: Two Dimension Recirculation Flow in a Reservoir - Kusuma, M. Syahril B. (Journal of Engineering and Technological Sciences, 2009)
An assessment of recirculation flow in Jatiluhur reservoir is conducted based on two dimensions turbulent Îº-Îµ model. The numerical model was developed using finite difference method where hydrodynamic equation was solved by the combination of Mc Cormack and splitting methods. The Îº-Îµ equation is solved using quickest scheme in convection term, central scheme in diffusion term and Euler scheme in reaction term. The simulations were done for maximum incoming flow during the rainy season and the dry season. Model results are compared to field measurement from which it is found that rainy season scenario has shown better agreement. Maximum incoming flow released in the rainy season could generate a boundary layer greater average velocity and more recirculation flow than that in the dry season. Further development is required to get more accurate results for the case with less average velocity.